2020
DOI: 10.1111/imr.12858
|View full text |Cite
|
Sign up to set email alerts
|

Immunometabolism: From basic mechanisms to translation

Abstract: Immunometabolism has emerged as a major mechanism central to adaptive and innate immune regulation. From early observations that inflammatory cytokines were induced in obese adipose tissue and that these cytokines contributed to metabolic disease, it was clear that metabolism and the immunological state are inextricably linked. With a second research wave arising from studies in cancer metabolism to also study the intrinsic metabolic pathways of immune cells themselves and how those pathways influence cell fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
190
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(206 citation statements)
references
References 97 publications
(157 reference statements)
3
190
0
Order By: Relevance
“…There has been emerging interest in determining what dictates the natural variability of immune cell subtype distributions, which are in large part driven by intrinsic genetic, environmental, and behavioral factors in humans 13 . In relation to the metabolic properties of specific immune cells subtypes, most data is derived from rodents or from human leukocytes often activated in vitro , which clearly demonstrates that immune cells exhibit specific metabolic requirements depending on their state 3, 54, 55 . Our analysis first confirmed the influence of sex and age on the proportions of circulating innate and adaptive cells, likely reflecting the effect of genetic and environmental factors throughout life.…”
Section: Discussionmentioning
confidence: 99%
“…There has been emerging interest in determining what dictates the natural variability of immune cell subtype distributions, which are in large part driven by intrinsic genetic, environmental, and behavioral factors in humans 13 . In relation to the metabolic properties of specific immune cells subtypes, most data is derived from rodents or from human leukocytes often activated in vitro , which clearly demonstrates that immune cells exhibit specific metabolic requirements depending on their state 3, 54, 55 . Our analysis first confirmed the influence of sex and age on the proportions of circulating innate and adaptive cells, likely reflecting the effect of genetic and environmental factors throughout life.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on immunometabolism have indicated that the metabolic states and immunological processes are inherently interconnected ( 6 ). In this scenario, metabolites derived from the host or microbiota regulate immunological responses during health and disease ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on immunometabolism have indicated that the metabolic states and immunological processes are inherently interconnected ( 6 ). In this scenario, metabolites derived from the host or microbiota regulate immunological responses during health and disease ( 6 ). Accordingly, in obese individuals, expanded adipose tissue at different locations, by initiating and perpetuating the inflammation, induces a chronic low-level inflammatory state that promotes IR ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the field of immunometabolism has provided data on the metabolic profile of immune cells and on the mechanisms through which cellular metabolism shapes the immune cells' activation state and function. 15 For example, in vitro classically activated M1 macrophages, use anaerobic glycolysis, protein and fatty acid (FA) synthesis metabolic pathways, 16 whereas alternatively activated M2 macrophages are mainly using oxidative phosphorylation (OXPHOS) for energy metabolism. 17 However, little is known about the programming and the specific metabolic phenotype of human macrophages in the context of cancer.…”
Section: Introductionmentioning
confidence: 99%